Service-Learning in Europe. Dimensions and Understanding From Academic Publication - Sotelino-Losada, Alexandre; Arbués-Radigales, Elena; García-Docampo, Laura; González-Geraldo, José L. (Frontiers in Education, 2021)
Service-Learning began within the framework of the New School in which constructivist experiential methodologies were particularly important following various studies, such as those by John Dewey and his “Learning by Doing” approach. From then on, this pedagogical practice has spread all over the world at varying rates. In Europe it was slower to spread than in the Americas, however it has been no less productive. In this regard it is especially interesting to look at the current state of the matter. The object of this study was to analyze the scientific publication in Europe since the year 2000 with a detailed bibliographic review of publications with roots in Europe. We examined the main databases and used an analysis matrix with various content levels. We found that Service-Learning has different names in Europe, and that there has been uneven epistemological advances depending on the countries examined. We also noted that it was about higher education that most literature had been published. One of our significant conclusions was the exponential growth of contributions over the last 20 years, particularly in Spain, which produced the most scientific literature on this topic. We believe that Service-Learning faces the challenge of effective consolidation based on educational quality criteria, and which includes combining elements of virtuality, reality, and academic rigor.